Systematic Literature Review: Gamification as a Strategy to Enhance Motivation in Learning Mathematics - Rizky Budi Prasetyo; Meiliasari (Universitas Negeri Surabaya, 2025)
This study aims to identify and analyze the implementation of gamification in mathematics learning as a strategy to enhance students' learning motivation. The method used is a Systematic Literature Review (SLR) with the SALSA approach (Search, Appraisal, Synthesis, and Analysis) to obtain a comprehensive and systematic synthesis of findings. A total of 17 scholarly articles published between 2015 and 2025 were analyzed based on four main focuses: the effectiveness of gamification, implementation challenges, types of learning media used, and gamification components that contribute to increased learning motivation. The analysis results show that gamification generally has a positive impact on learning motivation in the context of mathematics education. The application of elements such as points, levels, badges, leaderboards, challenges, immediate feedback, and visual narratives has been proven to enhance students’ attention, self-confidence, engagement, and learning satisfaction. However, the effectiveness of this strategy highly depends on the learning context, student characteristics, types of media used, and the quality of gamification design. Identified challenges include infrastructure limitations, low teacher competence in educational technology, misalignment of materials with the curriculum, and potential social and psychological impacts from the competitive systems implemented.